Royal Palace Location: The Case of The Sultanate of Perak - Mohd Jaki Mamat; Muhammad Firzan bin Abdul Aziz (Universitas Indraprasta PGRI, 2020)
Perak’s Malay Sultanate is known to have the longest root in the Malaysian Sultanate tradition with the most numbers of Sultans (35). Interestingly, 27 of them built a new palace, each for themselves, rather than using the inherited ones. However, those 27 locations of the royal palaces of the Perak’s Malay Sultanate are yet to be identified and recorded. This has called upon the needs to conduct a preliminary investigation on those locations based on scrutiny of secondary data (theoretically through old manuscripts and historical writings) and primary data (empirically through interviewing local people and utilising GIS technology). Analysis based on the data triangulations hence would provide a scientific and systematic inventory of the royal palaces of Perak’s Malay Sultanate.